Pengaruh Bauran Pemasaran Jasa Pendidikan Terhadap Citra Lembaga dalam Perspektif Masyarakat di MTs Negeri 2 Flores Timur - Akhmad, Tasyrifany (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This study aims to analyze the influence of the marketing mix of educational services on the image of institutions in MTs Negeri 2 East Flores from the perspective of the community. The educational marketing mix, which includes products, prices, locations, promotions, people, processes, and physical evidence, is expected to play an important role in shaping the public's positive perception of educational institutions. This study uses a quantitative approach with a survey method, data is collected through questionnaires distributed to respondents who are parents, prospective students, and members of the surrounding community. Data analysis was carried out using multiple linear regression to identify the influence of each variable of the marketing mix on the image of the institution. The results showed that the variables of product, promotion, and people had a significant effect on the image of the institution, while the variables of price, location, process, and physical evidence had a negligible influence. These findings indicate that the image of MTs Negeri 2 East Flores can be strengthened with a marketing strategy that emphasizes the quality of educational products, increased promotional activities, and the professionalism of educators and staff. Thus, this research contributes to the design of effective marketing strategies for Islamic educational institutions, especially in building a positive image in the eyes of the public